LA CONFIABILIDAD Y VALIDEZ DE LOS SONDEOS ELECTORALES. - Coronell, Daniel; Gonzalez, Olga (La Sociología en sus Escenarios, 2010)
Resumen. A continuación se presenta un conjunto de artículos repre4sentativos de la polémica presentada alrededor de los sondeos electorales y las encuestas de favorabilidad que últimamente se han presentado a través de los medios. Abstract. Polls must be make well and clarify what population represents. There is skepticism in examining the surveys methodologically? Perhaps it is necessary to begin to make this question. As a result of the columns that criticize the methodology used in the last electoral surveys arose a position according to which the surveys are not scrutinized, they are guaranteed.